Trade Preference Erosion Expanded Assessment of Countries at Risk of Welfare Losses - Lippoldt, Douglas C.. (OECD Publishing, 2005)
This paper presents additional findings from the on-going work of the OECD project on trade preference erosion. The purpose was to assess in more detail the situation of those preference-reliant countries seen as being most at risk of experiencing negative welfare effects from preference erosion as a consequence of multilateral tariff liberalisation (building on Lippoldt and Kowalski, 2005). Based on a selection criterion, 7 developing countries were chosen for inclusion in the present study: Bangladesh, Madagascar, Morocco, Mozambique, Tanzania, Uganda and Zambia. Using the standard GTAP database and model, the paper considers a scenario of multilateral tariff liberalisation involving a 50% linear reduction in the ad-valorem equivalent measure of protection. Whereas most developing regions experienced welfare gains as a consequence of such a scenario, the selected countries were found to be at risk of modest welfare losses, most of which were associated with tariff liberalisation by European Union countries (EU-15). Where negative welfare impacts occurred in the selected developing countries, they tended to be driven primarily by terms of trade losses (especially by negative export price effects). In line with the modest size of the estimated welfare losses, the overall impact in terms of structural adjustment -- as measured by an index of structural change -- tended to be relatively modest. For three of the seven developing countries, welfare losses primarily associated with the EU-15 tariff liberalisation are estimated to be more than fully offset by greater gains arising from improved market access in other sectors and markets
Keywords: Trade